Antecedents to foster green innovation: The role of green HRM, knowledge management and organizational culture - Nhan, Nguyen Thi Minh; Quyen, Nguyen Thi Tu; Phong, Le Ba (Edelweiss Applied Science and Technology, 2025)
Due to the important role of green innovation in helping firms achieve sustainable development, environmental protection, and a competitive advantage, this paper aims to investigate the influence of green human resource management (HRM) practices on green innovation through the mediating roles of green knowledge management (KM). This study also explores the potential moderating role of green culture in fostering the influence of green KM on aspects of green innovation, namely green product and green process innovation. The paper utilized a quantitative approach and Structural Equation Modeling to examine the relationships among the latent constructs using survey data collected from 305 participants across 118 firms. The empirical findings highlight the significant mediating role of green KM in linking the effects of green HRM practices to green product and process innovation. It also supports the moderating role of green culture in enhancing the influence of green KM on aspects of green innovation. The paper provides CEOs and managers with a better understanding of appropriate solutions and approaches to enhance firms’ green product and process innovation. Additionally, the paper contributes to advancing innovation theory by clarifying the antecedents and moderated-mediation effects in predicting green product and process innovation within the context of emerging markets.